LIQUISOLID TECHNIQUE: A NOVEL APPROACH FOR DOSAGE FORM DESIGN - Panda, Satyajit; Varaprasad, R.; Priyanka, K.; Swain, Ranjit P. (International Journal of Applied Pharmaceutics, 2017)
The liquisolid technique is a novel approach for delivery of drugs through the oral route. This technique is suitable for poorly soluble or water insoluble drugs, highly permeable drugs (BCS Class II drugs) and also for immediate or sustained release formulations. It is a novel "Powder Solution Technology" that involves absorption and adsorption efficiencies, making use of liquid medications, drug suspensions admixed with suitable carriers, coating materials and formulated into free flowing, dry looking, non-adherent and compressible powder forms. The design of liquisolid systems are mainly intended for enhancement of solubility, dissolution rate and bioavailability of poorly water-soluble and highly lipophilic drugs. Improvement in bioavailability may be due to increased surface area, increased aqueous solubility and increased the wettability of the drug. Liquisolid technique also has the potential to be optimized for the reduction of drug dissolution rate and thereby production of sustained release systems. Overall, liquisolid technique is a most promising and novel technique for enhancing the dissolution and bioavailability of poorly water soluble drugs and sustaining drug release from tablet matrices. The current review mainly focuses on theory and applicability of liquisolid compact technique towards solubility or bioavailability enhancement. Different carriers, solvents and coating materials employed are elucidated. Literature reports on the applicability of liquisolid compact techniques over a wide range of pharmaceutical formulations are also explicated.